Open services ecosystem supporting collaborative - F. G. Osório, A. Luís (2017)
The growing complexity of the information and communication technologies when coping with innovative business services based on collaborative contributions from multiple stakeholders requires novel and multidisciplinary approaches. Service orientation is a strategic approach to deal with such complexity, and various stakeholders’ information systems. Services or more precisely the autonomous computational agents implementing the services, provide an architectural pattern able to cope with the needs of integrated and distributed collaborative solutions. This paper proposes a service-oriented framework, aiming to support a virtual organizations breeding environment which is the basis to establish short or long term goal-oriented virtual organizations. The notion of integrated business services, where customers receive some value developed through the contribution from a network of companies is a key element.